Medical therapy for premature ejaculation - Mohee, Amar (SAGE Publications, 2011)
Premature ejaculation (PE) is a common male sexual dysfunction. Advances in PE research have been hampered owing to a nonstandardized definition of PE, until the definition by the International Society of Sexual Medicine (ISSM) in 2009. Once the diagnosis of PE is established through a thorough history, a variety of medical therapies is available, including tricyclic antidepressants, selective serotonin reuptake inhibitors (SSRIs), centrally acting opiates, phosphodiesterase 5 inhibitors and topical desensitizing creams. Most of these treatments increase the intravaginal ejaculation latency time (IELT) and patient satisfaction scores, with the most convincing evidence for SSRIs and topical creams. Daily SSRIs such as paroxetine, although efficacious, do have a substantial and prolonged side effect profile. Dapoxetine, which is a on-demand SSRI, is the only licensed drug for the treatment of PE, increasing IELT by a factor of 2.5 to 3 with limited and tolerable side effects. In the near future, the topical aerosol PSD502 is due to be licensed for the treatment of PE, increasing IELT by up to a factor of 6 but having minimal local and negligible systemic side effects.